Factors associated with facility childbirth and skilled birth attendance in Migori County, Kenya and the effect of Lwala Community Alliance intervention: a cross-sectional assessment from the 2019 and 2021 Lwala household surveys - Christina Hope Lefebvre; Joseph R. Starnes; Joseph R. Starnes; Aleksandra Jakubowski; Aleksandra Jakubowski; Alyn Omondi; Janet Manyala; Jane Wamae; Ash Rogers; Sandra Mudhune; Vincent Okoth; Vincent Were; et al. (Frontiers Media S.A., 2024)
BackgroundDespite evidence of the beneficial effects of skilled birth attendance (SBA) on maternal health and childbirth outcomes, there are disparities in access across counties in Kenya. These include Migori County which has historically recorded high maternal mortality rates. In 2007, the Lwala Community Alliance was founded to improve health outcomes in this county. The objective of this study is to provide a baseline status of facility childbirth and SBA in Migori and to characterize the effect of Lwala intervention on these outcomes.MethodsA cross-sectional household survey was designed for a 10-year study to evaluate the effectiveness of Lwala initiatives. The 2019 and 2021 household surveys were conducted in Lwala intervention wards and in comparison wards with sample sizes of 3,846 and 5,928 mothers, respectively. The survey captured demographic, health, and socioeconomic data at each household, data on SBA and facility childbirth, and explanatory variables. A generalized linear model was used to determine factors associated with SBA. A secondary trend analysis was conducted to determine change over time in the explanatory variables and SBA. To determine the change in SBA rate due to Lwala intervention, controlling for background temporal trends, a difference-in-differences (DiD) model compared SBA rates in intervention wards and comparison wards.ResultsSBA increased in all surveyed wards and across all explanatory variables from 2019 to 2021. The DiD analysis showed that the SBA rate increased more in Lwala intervention wards than in comparison wards (Adjusted Prevalence Rate Ratio 1.05, p < 0.001, 95%CI 1.03-1.08). The 2021 survey found the highest rates of both facility childbirths (97.9%, 95%CI 96.5-98.7) and SBA (98.2%, 95%CI 97.0-99.0) in North Kamagambo, the oldest ward of Lwala intervention. Higher educational status, four or more ANC visits, marriage/cohabitation, and wealth were significantly associated with increased SBA.ConclusionsWe provide the first quasi-experimental evidence that Lwala interventions are significantly improving SBA which may inform related initiatives in similar settings. The household-survey data provides a baseline for continued evaluation of Lwala programs, and the breakdown by ward allows for development of specific programmatic targets.